2006
DOI: 10.1021/bi061517b
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the β,γ Leaving-Group Bridging Oxygen Alters Nucleotide Incorporation Efficiency, Fidelity, and the Catalytic Mechanism of DNA Polymerase β

Abstract: DNA polymerase catalysis and fidelity studies typically compare incorporation of "right" versus "wrong" nucleotide bases where the leaving group is pyrophosphate. Here we use dGTP analogues replacing the beta,gamma-bridging O with CH2, CHF, CF2, or CCl2 to explore leaving-group effects on the nucleotidyl transfer mechanism and fidelity of DNA polymerase (pol) beta. T.G mismatches occur with fidelities similar to dGTP with the exception of the CH2 analogue, which is incorporated with 5-fold higher fidelity. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
244
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(261 citation statements)
references
References 51 publications
14
244
3
Order By: Relevance
“…Because single nucleotide insertion appears to be limited by a chemical step rather than conformational adjustments (16,49), the increased rate of insertion exhibited by the R258A mutant must be due to a change in the thermodynamic equilibrium with non-productive complexes rather than a kinetic change in the rate-limiting step. Scheme 1 illustrates structural adjustments that occur in the enzyme and/or substrates of the ternary substrate complex.…”
Section: Discussionmentioning
confidence: 99%
“…Because single nucleotide insertion appears to be limited by a chemical step rather than conformational adjustments (16,49), the increased rate of insertion exhibited by the R258A mutant must be due to a change in the thermodynamic equilibrium with non-productive complexes rather than a kinetic change in the rate-limiting step. Scheme 1 illustrates structural adjustments that occur in the enzyme and/or substrates of the ternary substrate complex.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, recent experimental studies (Sucato et al 2007(Sucato et al , 2008) presented a new probe for leaving group effects during the nucleotide transfer reaction catalyzed by Pol b, in which the b,c-bridging oxygens of the dGTP were replaced by a series of substituted methylene groups (X=CYZ, where Y and Z=H, halogen or another substituent, Fig. 45).…”
Section: Some Points On the Interpretation Of Lfer In Polymerasesmentioning
confidence: 99%
“…Earlier structures of DNA pol β with incoming nucleoside triphosphate analogs with CF 2 substituted for O α;β or O β;γ indicated that this substitution is well tolerated (35,36). Recently, even O β;γ has been substituted by CXY group (X;Y ¼ H, F, Cl, Br, and /or CH 3 ) (37, 38).…”
mentioning
confidence: 99%